Penerapan Peramalan Penjualan Pada Anggaran Penjualan Sebagai Dasar Dalam Penyusunan Anggaran Produksi dan Anggaran Biaya Produksi - Nurul Febriyanti Hazmi; Arwan Gunawan; Etti Ernita Sembiring (Indonesian Accounting Literacy Journal, 2023)
The existence of such planning will have an impact on increasing the quality of UMKM and can create profits, with UMKM planning being done to define policies and also good internal control. The existence of a budget is one of the planning instruments. Sales budgets, production budgets, and production cost budgets are all examples of budgets. The goal of this research is to find the best sales forecasting method for the Pabrik Tahu Mahrup Cibogo, as well as to prepare a production budget and production cost budget. The author employs a descriptive method with a quantitative approach in this research. Sources of data obtained by the author by means of interviews, observation, and also documentation. The data used in this reseacrh is historical sales data from June 2020 to May 2021. Based on the results of the research, the quadratic method is the right method to be used in sales forecasts because the smallest SKP value is 10.84116. The forecasted number of yellow tofu items sold over the next year is 3,866 tofu prints, or Rp.193,296,953. The production budget is made based on the sales budget that has been prepared and also management policies.According to the production cost budget, the Pabrik Tahu Mahrup Cibogo will incur Rp. 229.252.927in costs for the coming year.